Parent participation practices and subjectivities: New Zealand primary education 1988-2017 - Smith, Megan (Journal of educational administration and history, 2021)
Parent participation with learning, defined here as parental engagement, has been a particular educational policy focus in many countries in recent decades. Grounded in neoliberal education sector reforms, the relationship between parents, learning, and schools has been reframed over this period. Using a genealogical approach, this article analyses parental engagement policies and practices, and the subjectivities these have engendered, in relation to New Zealand primary education 1988-2017. An overview of contemporary policies and practices, is followed by a commentary on what is found to be the two emergent, and dominant, parent subjectivities: parents as consumers, and as governors. These are considered alongside other longer-standing parent participation subjectivities. The article concludes by arguing that parental engagement is dominated by emergent subjectivities, and that these are contributing to inequalities and constraining engagement. The findings call for greater consideration of the diverse set of potential subject positions in both policy and practice.